Plant Based Extracts and Chemical Interventions for Management of Pestalotiopsis psidii- A Study on Guava Fruit Canker - Bhogal, Shivangi; Jarial, Kumud; Jarial, R. S. (International Journal of Bio-resource and Stress Management, 2025)
An investigation was conducted during March, 2019–February, 2020 in the Research Laboratory, Department of Plant Pathology, College of Horticulture and Forestry, Neri, Hamirpur, Himachal Pradesh, India, to evaluate the in vitro efficacy of different plant-based extracts and chemical fungicides against Pestalotiopsis psidii, the causal organism of guava fruit canker. A total of four plant-based extracts and one natural product were evaluated for their antifungal properties. Among these, Azadirachta indica (neem) extract and 10 days old sour buttermilk inhibited the growth of P. psidii by 25.11 and 76.39%, respectively. In contrast, synthetic fungicides such as CabrioTop, Chlorothalonil, Tilt, Ridomil MZ, Bavistin, Blitox and Contaf demonstrated complete inhibition of the pathogen under invitro conditions, indicating their strong antifungal efficacy. Among the tested fungicides, CabrioTop was the most effective fungicide in both prophylactic (preventive) and curative (therapeutic) treatments. It not only completely suppressed the growth of P. psidii but also extended the incubation period (33.30 and 29.72 h) of the disease, thereby reducing disease severity (69.03 and 75.82%, respectively). In conclusion, CabrioTop could serve as a highly effective chemical control measure against guava fruit canker, providing rapid and dependable disease suppression in field conditions while, neem extract and sour buttermilk emerge as eco-friendly alternatives, offering antimicrobial properties that may reduce disease incidence without posing harm to the environment.